Recovery in vivo of nonculturable subpopulation of Salmonella enterica - Yudin, I (Annals of Mechnikov’s Institute, 2020)
Introduction. As one of mesophilic, easily cultivated species of pathogenic bacteria, Salmonella enterica transformed into viable but nonculturable (VNC) state in response to environmental stresses, including action of biocides. The cells in this state, preserve the integrity of membranes and metabolism of some, but not detected by conventional methods of cultivation. Some researchers suggest that the evolutionary significance of this phenomenon is part of an adaptive response aimed at long-term survival of bacteria in adverse conditions; others argue that it is the result of stochastic cellular damage, in which nonculturable cells are in a state of gradual death. In any case, the phenomenon of existence VNC pathogens if they retain the ability to restore its growth in vivo is a significant problem in medicine, pharmaceutical, veterinary, food industry. VNC subpopulation of S. enterica was obtained under action of ethanol. In this paper was investigated in vivo resuscitation VNC S. enterica using intraperitoneal injection of mice. Materials and methods. Obtaining of stressful S. enterica populations. Bacteria were grown to exponential phase in broth Luria–Bertani (LB). To 1.0 ml sample suspension diluted to 1.5 × 106 cells/ml was added 1.0 ml of ethanol at a concentration of 40 % (v/v). After exposure of 10 to 600 minutes in the suspension were added 8.0 ml of phosphate buffered saline (FBS), washed by centrifugation (4500 g for 5 minutes) and serially diluted at a ratio of 1:10 (v/v) samples were stained with LIVE/DEAD BacLight (produced by "Invitrogen", USA), filtrated on membrane filters for fluorescence microscopy and parallel plated on LB agar cup to determine colony-forming units (CFU) per ml. In vivo resuscitation VNC S. enterica was made following way. Three groups of animals were inoculated by intraperitoneal injection: 1) 103 culturable cells (0.1 ml suspension containing 104 CFU / ml); 2) 103 VNC cells (0.1 ml suspension containing 104 cells / ml of nonculturable population); 3) 103 inactivated cells (pasteurization at 60 °C in 70 % ethanol, 30 min). Mice were observed daily for 14 days to register the death and extraction of internal organs. Liver and spleen of dead mice were removed and homogenized in 1.0 ml of FBS to detect restored Salmonella cells by seeding on selective medium bismuth sulfite agar (BSA). Results and discussion. In this study S. enterica cells in the exponential growth phase, exposed to ethanol (final concentration 20 %) lost culturability within 60 minutes. After 50 minutes of exposure with ethanol culturability of bacterial suspensions was outside evaluation cup method. At the same time, the integrity of cell membranes was determined at 4 log10 cells/ml. Bacteria that become VNC state can restore culturability. Thus, the state is reversible. Importantly, the resuscitation of VNC in vitro, which is achieved by simply eliminating or VNC induction factor (increasing the growth temperature, availability of nutrients) or more complex conditions such as a combination of environmental and chemical stimuli, does not reveal the full pathogenic potential of resuscitated bacteria. Therefore, the process of Salmonella resuscitation in vivo, we studied on infection model in mice.In experiments in vivoS. enterica resuscitation death of test animals was observed in 13.3% (p < 0.05) during the observation period, with 100% mortality in the group of animals infected with a suspension of living culturable cells Salmonella and 100% survival of the animals in the control group (who received injections of inactivated bacteria). From the dead mice from homogenates of internal organs plated recovered salmonella, which was confirmed by their growth on BSA.Conclusions. Under conditions in vivo recovery process VNC S. enterica cells can occur, but with low intensity in healthy mice (at 13.3%, p <0.05). However, these cells retain pathogenic potential and can represent a danger if their underestimation. We can assume that the bacteria lose their virulence in part, but manifest it in individuals with a weak immune response.